Exploration of Crucial Mediators for Carotid Atherosclerosis Pathogenesis Through Integration of Microbiome, Metabolome, and Transcriptome - Ji, Lei; Chen, Siliang; Gu, Guangchao; Zhou, Jiawei; Wang, Wei; Ren, Jinrui; Wu, Jianqiang; Yang, Dan; Zheng, Yuehong (Frontiers in Physiology, 2021)
Background: Carotid atherosclerosis (CAS) is an important cause of stroke. Although interactions between the gut microbiome and metabolome have been widely investigated with respect to the pathogenesis of cardiovascular diseases, information regarding CAS remains limited. Methods: We utilized 16S rDNA sequencing, and untargeted metabolomics to investigate the alterations in the gut microbiota and plasma metabolites of 32 CAS patients and 32 healthy controls. The compositions of the gut microbiota differed significantly between the two groups, and a total of 11 differentially enriched genera were identified. In the metabolomic analysis, 11 and 12 significantly changed metabolites were screened in positive (POS) and negative (NEG) modes, respectively. α-N-Phenylacetyl-L-glutamine was an upregulated metabolite in CAS patients that was detected in both POS and NEG modes and had the highest |log2(fold-change)| in POS mode. In addition, transcriptomic analysis was performed using the GSE43292 dataset. Results: A total of 132 differentially expressed genes (DEGs) were screened. Among the upregulated DEGs in CAS patients, FABP4 exhibited the highest |log2(fold-change)|. Furthermore, FABP4 was positively associated with Acidaminococcus and had the highest Spearman’s correlation coefficient and the most significant p-value among the microbiota-DEG pairs. Conclusion:In this study, we investigated the potential "microbiota-metabolite-gene" regulatory axis that may act on CAS, and our results may help to establish a theoretical basis for further specialized study of this disease.